To solve the equation 4(3x-2) = -24, we can follow these steps:
1. Start by distributing the 4 to the terms inside the parentheses:
4 * 3x - 4 * 2 = -24
12x - 8 = -24
2. Next, isolate the term with the variable.
Add 8 to both sides of the equation to move the constant term to the right side:
12x - 8 + 8 = -24 + 8
12x = -16
3. Finally, solve for x by dividing both sides of the equation by 12:
12x/12 = -16/12
x = -4/3
Therefore, the solution to the equation 4(3x-2) = -24 is x = -4/3.
consider this equation: 4(3x-2)=-24
3 answers
consider this equation: 4(3x-2)=-24
part one. what is your first step in solving the equation?
part two. how would you isolate the variable and solve for x after you have completed part one?
part one. what is your first step in solving the equation?
part two. how would you isolate the variable and solve for x after you have completed part one?
Part one: The first step in solving the equation is to distribute the 4 to the terms inside the parentheses.
Part two: After distributing 4 to 3x and -2, the equation becomes 12x - 8 = -24. To isolate the variable x, we need to get rid of the -8 term on the left side. We do this by adding 8 to both sides of the equation:
12x - 8 + 8 = -24 + 8
This simplifies to:
12x = -16
Finally, to solve for x, we divide both sides of the equation by 12:
12x/12 = -16/12
The 12s cancel out on the left side, leaving us with:
x = -16/12
This can be simplified to:
x = -4/3
Part two: After distributing 4 to 3x and -2, the equation becomes 12x - 8 = -24. To isolate the variable x, we need to get rid of the -8 term on the left side. We do this by adding 8 to both sides of the equation:
12x - 8 + 8 = -24 + 8
This simplifies to:
12x = -16
Finally, to solve for x, we divide both sides of the equation by 12:
12x/12 = -16/12
The 12s cancel out on the left side, leaving us with:
x = -16/12
This can be simplified to:
x = -4/3